2012
DOI: 10.1155/2012/345762
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and Two-Temperature Zone Selenization of Mo Layers

Abstract: Glass/Mo, Mo foil, glass/Mo/In, and glass/Mo/Cu stacked layers were selenized in closed vacuum tubes by isothermal and/or two-temperature zone annealing in Se vapors. The selenization process was studied dependent on Se vapor pressure, temperature and time. Samples were selenized from 375 to 580°C for 30 and 60 minutes. The applied Se pressure was varied between 130 and4.4⋅103 Pa. The increase of MoSe2film thickness was found to depend on the origin of Mo. MoSe2thicknessdLon Mo-foil was much higher than on spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As for concern of possible secondary phases in CZGSe film, it is reported that secondary phases, Cu 2 Se or CuSe 2 , has Raman peaks at 270 cm −136 and peaks at 147 and 260 cm −1 are assigned to CuSe. 37,38 MoSe 2 can be identified by Raman peaks at 169, 240, 280 and 350 cm −139, 40 and ZnSe phase can be at 210 and 254 cm −1 . 41 Herein, we just observed Cu 2 Se or CuSe 2 secondary phase in Raman spectra of CZGSe thin films.…”
Section: Crystal Structure and Phasementioning
confidence: 99%
“…As for concern of possible secondary phases in CZGSe film, it is reported that secondary phases, Cu 2 Se or CuSe 2 , has Raman peaks at 270 cm −136 and peaks at 147 and 260 cm −1 are assigned to CuSe. 37,38 MoSe 2 can be identified by Raman peaks at 169, 240, 280 and 350 cm −139, 40 and ZnSe phase can be at 210 and 254 cm −1 . 41 Herein, we just observed Cu 2 Se or CuSe 2 secondary phase in Raman spectra of CZGSe thin films.…”
Section: Crystal Structure and Phasementioning
confidence: 99%
“…On the one hand, controlling the annealing temperature and time are the common routes to obtaining high‐quality absorbers and reducing the formation of Mo(S x ,Se 1− x ) 2 . [ 18,27 ] Although decreases in annealing time and temperature could reduce the formation of Mo(S x ,Se 1− x ) 2 effectively, it would also lower the crystalline quality of the absorber. [ 28 ] On the other hand, the insertion of a barrier layer on top of Mo is widely adopted to modify the back contact.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study, where Mo films were selenized to form MoSe 2 , has been reported in the literature. 12 In this study, the activation energy of MoSe 2 growth was determined 0.7 6 0.1 eV by fitting a MoSe 2 thickness vs. temperature (1/T) with a single exponent over the entire annealing temperature range used (375-580 C), implicitly assuming a priori that a limiting case-where one kinetic process is much slower than the others connected in series-was in play. Our finding that the process is diffusion-limited now supports their assumption and indeed their estimated activation energy of 0.7 6 0.1 eV is very close to our estimation of E D2 .…”
mentioning
confidence: 99%